Propionic acid beneficially modifies osteoporosis biomarkers in patients with multiple sclerosis. - Duscha, Alexander; Hegelmaier, Tobias; Dürholz, Kerstin; Desel, Christiane; Gold, Ralf; Zaiss, Mario; Haghikia, Aiden (Therapeutic Advances in Neurological Disorders, 2022)
BACKGROUND: The impact of the gut and its microbiota are increasingly appreciated in health and disease. Short-chain fatty acids (SCFAs) are among the main metabolites synthesized from bacterial fermentation. Recently, we showed the anti-inflammatory and potentially neuroprotective effect of propionic acid (PA) in multiple sclerosis (MS). Osteoporosis is one of the most common co-morbidities for MS patients with limited therapeutic options available. Osteoporosis is closely linked to an imbalance of cells of the immune system and an immune-mediated impact on bone structure via the gut has been shown. Interestingly, intake of SCFA leads to bone mass increase and concomitant reduction of inflammation-induced bone loss in mice. OBJECTIVE: To determine the impact of PA supplementation on markers of bone metabolism in MS patients. METHODS: We investigated the influence of 14 days supplementation with PA on bone metabolism in 20 MS patients. To this end, β-CrossLaps and osteocalcin, established markers of bone metabolism, were measured in serum before and after PA intake and correlated with phenotypic and functional immunodata. RESULTS: Supplementation with PA induced a significant increase in serum levels of osteocalcin, a surrogate marker for bone formation. Levels of β-CrossLaps, a marker for bone resorption, were significantly decreased after therapy. Regulatory T-cell (Treg) numbers and suppressive capacity positively correlated with serum levels of osteocalcin while Th17 cell numbers showed an inverse correlation. Our findings are in line with animal studies showing that SCFA induced increased bone formation and reduced bone resorption. CONCLUSION: In addition to its immune regulatory, disease-modifying effect on MS disease course, supplementation with PA beneficially influences serum levels of β-CrossLaps and osteocalcin and may thus also protect against osteoporosis, a common co-morbidity in MS.
EVALuna2:513178